2022
DOI: 10.7759/cureus.22827
|View full text |Cite
|
Sign up to set email alerts
|

Sjögren’s Syndrome Complicated With Sarcoidosis With a Repetitive, Prolonged, Non-productive Cough

Abstract: Sjögren's syndrome and sarcoidosis are systemic immune-mediated diseases of unresolved pathogenesis, with dry cough being a symptom of both diseases. Due to the low pre-test probability of the diseases, they are not considered in the first differential diagnosis of prolonged non-productive cough. We report the case of a 33-year-old woman presenting with an intermittent, non-productive cough, diagnosed with Sjögren's syndrome coexisting with sarcoidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Sarcoidosis is a systemic granulomatous disease. CD4+ T cells interact with antigen-presenting cells to initiate the formation of granuloma plays a role in its pathogenesis 1 . Dyspnoea, which worsens with activity, persistent dry cough, chest pain; and wheezing are the manifestations of pulmonary sarcoidosis 11 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Sarcoidosis is a systemic granulomatous disease. CD4+ T cells interact with antigen-presenting cells to initiate the formation of granuloma plays a role in its pathogenesis 1 . Dyspnoea, which worsens with activity, persistent dry cough, chest pain; and wheezing are the manifestations of pulmonary sarcoidosis 11 .…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have reported the coexistence of sarcoidosis and SS 1 , 6 , 12 , 13 There is a higher prevalence of articular and ocular involvement, anti-nuclear antibodies, rheumatoid factor, and positive anti-Ro/SSA antibodies in patients with coexisting sarcoidosis and SS 10 . Although anti-nuclear antibodies could be detected in sarcoidosis, anti-Ro/SSA antibodies were uncommon.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In two thirds of cases, sarcoidosis was diagnosed concomitantly with SS or during the follow-up of patients with an already diagnosed SS while a superimposed diagnosis of SS during the follow-up of patients firstly diagnosed with sarcoidosis was less frequently observed. To date, less than 39 cases of coexisting SS with sarcoidosis had been reported (Supplementary Table S1) (13,(21)(22)(23)(24)(25)(26)(27)(28). Therefore, the coexistence of the two diseases should be considered a rare event.…”
Section: Discussionmentioning
confidence: 99%